Provision of Healthy Menu Innovation for Development of Children in Early Childhood Education - Febry Mutiariami Dahlan; Jenny Anna Siauta (Rajaki of Tulip Medika Publisher, 2026)
The quality of health and development among children in later stages of life is greatly influenced by early childhood education (PAUD). At this stage, balanced nutrition is very important for building healthy living habits, physical growth, and cognitive development. However, the common problem is that children do not like to eat vegetables. As a result, they do not get enough nutrients, especially vitamins and fiber. Therefore, new healthy and appealing menu must be created. One of the innovations offered by this community service program was made healthy carrot gummies. Carrots were chosen because they contain vitamin A, beta-carotene, fiber, and other essential nutrients that were important for maintaining eye health, boosting the immune system, and supporting children's growth. Thru more preferred form and taste, processing carrots into gummies was expected to increase children's interest in eating vegetables. The aim of this service is to enhance children's interest in vegetable-based products, improve the nutritional quality of children in early childhood education, and provide easily accessible and healthy snack options. The expected benefits are an increase in nutritional intake, especially vitamin A, and the establishment of healthy eating habits from a young age. This activity was conducted with twenty preschool children thru various steps. They selected the raw materials, made carrot gummies, conducted trials to see if the children accepted them, and evaluated their reactions. The results of activity showed that children prefer to eat healthy snacks that were visually appealing. Additionally, parents and early childhood educators learned about the importance of balanced nutrition. Overall, this activity influences children's eating patterns and family nutrition awareness. It is hoped that similar activities can be conducted sustainably so that the habit of consuming healthy menus among early childhood education (PAUD) children can be consistently formed.